Effect of Porosity on the Peristaltic Pumping of a NonNewtonian Fluid in a Channel - Gc Sankad; Asha Patil (Journal of New Results in Science)
The peristaltic flow of a non-Newtonian fluid in a flexible channel, with permeable walls, under the assumptions of long wavelength and low Reynolds number is studied. The pressure rise and frictional force are discussed for various parameters of interest like yield stress, Darcy number etc. through graphs. It is observed that with increase in porosity, there is pressure drop in the pumping region while there is a pressure rise in the co-pumping region. The behavior of the volume flow rate𝑄̅is similar for both the pressure difference and frictional force, forthe variation of all the parameters.